Neonatal gastric outlet obstruction by isolated pyloric atresia, an often forgotten diagnosis. Issue 2 (3rd March 2016) - Mboyo, Antoine; Clermidi, Pauline; Podevin, Guillaume; Patkowski, Dariusz; Baglaj, Maciej; Gerus, Sylwester; Lalioui, Abdelfetah; Napoli-Cocci, Stéphan de; Robert, Michel
Abstract: Background : Pyloric atresia (PA) is a rare condition, and may be misdiagnosed and especially confused for duodenal atresia pre-operatively. We looked for clues to avoiding pre-operative misdiagnosis and hence allow the best neonatal medical and surgical management.Methods : A retrospective case-note review was carried out of the five patients managed in four centres with the diagnosis of isolated PA. We focused on antenatal ultrasound findings, postnatal clinical and radiological features, operative findings, surgical procedures and outcomes.Results : Four patients had polyhydramnios and one double bubble sign on antenatal ultrasound. After birth, non-bilious vomiting and upper abdominal distension were the main symptoms. Gastric decompression showed non-bilious gastric fluid. Radiological findings were a large gastric air bubble with no gas beyond in all cases. The diagnosis of duodenal atresia was postulated at first in all cases. The diagnosis of PA was established peroperatively. One patient referred late, died 13-day post-operatively of cardiopulmonary failure secondary to a severe pneumonia that may be related to aspiration syndrome. Outcomes were otherwise satisfactory.Conclusions : Even though it is a rare diagnosis, PA has a specific clinical and radiological presentation underlined here that should be kept in mind when managing a neonate with a gastric outlet obstruction.